Reducing Re-arrest Through Community-Led, Police-Initiated Restorative Justice Diversion Tailored for Youth - Beckman, Kara J. (Crime & delinquency, 2024)
Restorative justice diversion aligns with youths’ developmental needs more than traditional approaches. However, there is a research gap regarding its effectiveness among diverse youth, and when initiated by police. This study evaluated misdemeanor cases that occurred in Minneapolis between September 2014 and December 2018 finding that youth who participated in restorative justice diversion after arrest were less likely to experience re-arrest in the following year compared to those processed traditionally. Positive program impacts for Black and American Indian youth demonstrate RJ diversion can be effective with diverse youth while differences in rates of successful diversion by participating community agency highlight opportunities for further study. This study demonstrates the importance of continuing to understand and expand restorative justice diversion with youth.